Neue Grauzonen der Technikgeschichte - Möser, Kurt (Technikdiskurse : Karlsruher Studien zur Technikgeschichte / Hrsg.: Karlsruher Institut für Technologie (KIT), Institut für Technikzukünfte, Teilinstitut für Geschichte, 2018)
Kurt Möser visits new fields of our technological cultural past. Cameras, airports, racing boats or ironclads become significant. His essays stimulate methods and new themes. Crime end technology, magic and aeronautics, the birth of the computer from battleship calculators, excentric usters - these are some of the subjects, organized in things, spaces, persons, unpleasances, old and new, individual themes.